STOCK-PILED ORGANIC AND MINERAL MIXTURES FOR POT-HOLE REPAIRING OF ASPHALT AND CONCRETE PAVEMENTS - A. Yu. Igoshkina (Наука и техника)
Despite of application of modem materials and methods for construction and repair of asphalt and concrete road pavement, the problem pertaining to removal of surface defects and consequently requirement for effective pot-hole repairing methods still remains an actual one and it is considered as one of the factors that ensures safety traffic conditions.Perspective repairing material has been obtained (cold stock-piled organic and mineral mixtures), which does not require special paving equipment, and which is characterized by a wide range of operational temperatures and excellent thixotropic properties. This allows to solve a problem to prevent asphalt and concrete pavement defects in the seasons of spring and winter. Possibility of long-term storage period and all-year-round application of repairing mixtures increase traffic safety and especially in the period of emergency pot-hole removal on asphalt road pavements.